Pharmacist-led multidisciplinary approach in preventing strokes in people with atrial fibrillation. (3rd October 2022) - Patel, M; Ali, S; Robson, J; Clements, R; Theodoulou, A; Wright, P; Kearney, M; Patel, R; Sohaib, A; Antoniou, S
Abstract: Background/Introduction: Targets set by Public Health England (PHE) state that 90% of patients with atrial fibrillation (AF) are expected to receive anticoagulation by 2029. In 2019/2020, across three London boroughs serving a population of 770, 000, the percentage of AF patients at high risk of stroke (CHA2DS2VASc>2) anticoagulated was below the target set by PHE. In addition, optimisation of risk factors can significantly reduce the risk of cardiovascular disease and associated mortality in these patients. Purpose: To provide specialist input from a cardiovascular pharmacist to prevent AF-related strokes through improvement of anticoagulation rates and optimisation of cardiovascular risk factors in patients with AF across three London boroughs over one year, as well as minimising bleed risk in patients on dual antithrombotic therapy. Methods: A specialist cardiovascular pharmacist was commissioned to identify high-risk AF patients (CHA2DS2VASc>2) by working with primary care clinicians. Utilising "proactive care frameworks" created by UCLPartners and Clinical Effectiveness Group Queen Mary University of London, patients were stratified and prioritised for review. Patients not on anticoagulation were deemed to be at highest risk, requiring an urgent review to assess suitability for anticoagulation. A virtual multidisciplinary team (MDT) would review any complex patients and agree an action plan. Patients on dual antithrombotic therapy were also assessed to determine if antiplatelet therapy was indicated to minimise risk of major bleeding. All AF patients were reviewed for suitability of statin initiation to optimise cardiovascular risk prevention. Results: At baseline, 86% (7581/8582) of AF patients with a CHA2DS2VASc>2 across the three boroughs were anticoagulated. 1001 patients were reviewed by a specialist pharmacist, with 84% (841/1001) of patients having a CHA2DS2VASc between 2–5, and 28% (280/1001) on antiplatelet monotherapy. Analysis at 12 months following intervention reported that 95% (7888/8280) of AF patients with a CHA2DS2VASc>2 were suitably anticoagulated, an improvement of 9%. 6% (61/1001) of patients were switched from antiplatelets and 25% (246/1001) were newly initiated on anticoagulation. 13% (130/1001) of patients required specialist MDT input to determine appropriateness for anticoagulation initiation. There was also a reduction in dual anticoagulation and antiplatelet therapy from 429 to 252 patients (41% reduction). Lastly of those reviewed, 2609 patients received a recommendation to start a statin for either primary (n=1981) or secondary prevention (n=628). Conclusion(s): Provision of a specialist cardiovascular pharmacist supported a multidisciplinary workforce to significantly improve and optimise cardiovascular risk, and reduce the risk of stroke in this high-risk population for people with AF across all three boroughs. By extrapolating these results nationally, 3600 strokes could be averted over 18 months. Funding Acknowledgement: Type of funding sources: None.